A review of cardiopulmonary research in brazilian medical journals: clinical, surgical and epidemiological data (Clinics, 2010)
Research in the field of cardiopulmonary disease in Brazil has been very active in recent decades. The combination of PUBMED, SCieLO, open access and online searching has provided a significant increase in the visibility of Brazilian journals. This newly acquired international visibility has in turn resulted in the appearance of more original research reports in the Brazilian scientific press. This review is intended to highlight part of this work for the benefit of the readers of "Clinics." We searched through PUBMED for noteworthy articles published in Brazilian medical journals included in the Journal of Citation Reports of the Institute of Scientific Information to better expose them to our readership. The following journals were examined: "Arquivos Brasileiros de Cardiologia," "Arquivos Brasileiros de Endocrinologia e Metabologia," "Brazilian Journal of Medical and Biological Reviews," "Jornal Brasileiro de Pneumologia," "Jornal de Pediatria," "Revista Brasileira de Cirurgia Cardiovascular," "Revista da Associação Médica Brasileira," Revista da Escola de Enfermagem U.S.P." and "São Paulo Medical Journal." These journals publish original investigations in the field of cardiopulmonary disease. The search produced 71 references, which are briefly examined.